Gestão de parcerias: o exemplo das políticas para a infância - Dowbor, Ladislau (Revista Administração em Diálogo - RAD, 2008)
O Estado, as empresas e as organizações da sociedade civil obedecem a dinâmicas, ou a culturas organizacionais, bastante diferentes, olham-se freqüentemente com desconfiança, e a construção das articulações, das alianças, das sinergias no desenvolvimento social é ao mesmo tempo necessária e complexa. Como construir estas aproximações, como ultrapassar as desconfianças, como evitar as sobreposições, como criar respeito e confiança entre culturasorganizacionais diferentes, como se proteger dos excessos do reunionismo e do populismo, mas ao mesmo tempo garantir processos democráticas e eficiência nas ações, tudo isto sãoquestões centrais neste trabalho. A criança é do interesse de todos nós, e as políticas a ela destinadas têm propiciado expderiências interessantes sobre como organizar processoscolaborativos de gestão, nestas novas arquiteturas organizacionais que são os sistemas de alianças e parcerias.Palavras-chave: economia social, participação, empoderamento, gestão social AbstractThis is part of an exploratory study about how to manage partnerships, alliances and the wide range of types of inter-institutional organization. These organizational forms are, on the one hand, proving rich in synergies, especially when social policies are concerned; on the other hand, they make it more difficult to define the focus of action, tend to disperse our attention into a multitude of diverse relations, and in fact represent a challenge to traditional forms of management.We do have considerable knowledge about how to manage a private corporation or a government agency, and we are learning to manage non-profit organizations. However, tomanage the intricate relationships and interactions of these various areas, which obey to very different dynamics, have different internal cultures, and have often inherited a tradition of mutual distrust, constitutes a different challenge, and the reality is that we are stepping on fragile ground, frequently exploring new management paradigms. And it is not just a matter of management techniques: it is also an issue of values such as trust, collaboration, solidarity, transparency – without which no partnership works – in a world in a sense reduced to the logic of competition, of unilateral advantages, and to the so-called “global rat race”. The entire process analyzed here is immersed in this contradictory environment.Key words: social economics, social management, empowerment, participation